CRYSTAL STRUCTURE AND COMPRESSIBILITY OF A TWO-LAYER POLYTYPE OF PSEUDOWOLLASTONITE (CASIO3) - Yang H.; Prewitt C.T. (My University, 1999)
The crystal structure of a synthetic two-layer polytype of CaSiO 3 pseudowollastonite was determined using single-crystal X-ray diffraction data. It is monoclinic with space group C2/c and unit-cell parameters a = 11.8322(6), b = 6.8624(8), c = 10.5297(5) Aa, beta = 111.245(8) degrees , and V = 796.9(1) Aa 3 . The material is isostructural with two-layer SrSiO 3 and SrGeO 3 and has basic structural features similar to those found in four-layer CaSiO 3 pseudowollastonite, except for the stacking sequence of layers of CaO 6 octahedra and Si 3 O 9 ternary rings. The compressibility of the structure was measured up to 9.94 GPa and no phase transition was observed. With increasing pressure, all unit-cell parameters decrease nonlinearly with a positive curvature. The axial compression ratios at room pressure are beta a :beta b :beta c = 2.25:2.36:1.00 and the bulk modulus, K T , is 86(1) GPa with K' = delta K T /delta P = 3.8(4).